Performance of Laying Hens Fed Varying Dietary Levels of Bambara (Voandzeia subterrenea Thouars) Offals - Onyimonyi, A.E.; Ugwu, S.O.C. (International Journal of Poultry Science, 2007)
A feeding trial was conducted to evaluate the performance of laying hens fed varying dietary levels of Toasted Bambara Offals (TBO). The TBO was included in the diet at five levels of 0, 5, 10, 15 and 20 percent. A total of ninety laying hens on their eight week of lay were used for the trial that lasted for 133 days. The ninety birds were randomly assigned to the five dietary levels (0, 5, 10, 15 and 20 percent) with 18 birds per levels. Each dietary level was further replicated four times in a completely randomized design. Results showed that egg weight (g), yolk weight (g) and albumen weight (g) were significantly (P<0.05) affected by treatments. Values of 61.38, 64.00, 64.67, 65.00 and 68.45 g was recorded as egg weights for birds on the 0, 5, 10, 15 and 20 percent diets respectively. Yolk weight was 16.53, 16.50, 16.43, 17.83 and 18.07 for 0, 5, 10, 15 and 20 percent diets respectively and albumen weight of 37.78, 39.51, 39.44, 39.82, 43.09 was also observed in that order. The cost of feed (N) significantly (P<0.05) decreased as level of TBO in the diets increased. Cost of feed consumed/bird (N) significantly decreased as level of TBO in the diets increased. Total eggs produced/bird followed the same trend. Profit recorded from sale of eggs was significantly (P<0.05) highest at the 10 percent level. A value of N 1139.81 was recorded for the 10 percent diet, as compared to N1120.13; N1126.96, N1089.75 and N1083.87 recorded for the control, 5, 15 and 20 percent diets respectively. The results of the present study showed that TBO can be fed at 10 percent to laying hens to replace substantial levels of the more costly maize and soyabean meal. This level of feeding will ensure optimum performance and economic benefit to the farmer.